LANGKAH INDONESIA MENGHADAPI TUDUHAN UNI EROPA TERHADAP PRAKTEK DUMPING PRODUK BIODIESEL INDONESIA TAHUN 2013 - Rostia, Yeni Ariza; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to understand what Indonesian’s Steps Facing European Union Allegations Against Dumping Practies Indonesian Biodiesel Product In 2013. Indonesia as a biofuel exporting countries in the world, even 90% of EU imports of biodiesel from Indonesia. However, the European Union claim that Indonesia has been selling biodiesel to EU members at a price below their normal value. According to the results of the EU investigation, imposition of additional import duties for the biodiesel industry in the European Union harmed by imports of biodiesel from Indonesia and Argentina.This research theoretically has built with Liberalism perspectives on International Relations and supported by Absolute Advantage theory Adam Smith. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data is gotten and collected from the journal books, the last thesis and then from internet has related to the problems.the research found that Indonesian’s Step Facing European Union Allegations Against Dumping Practies Indonesian Biodiesel Product In 2013 through suing the EU to the World Trade Organization. Indonesia suing the EU through the secretariat of the World Trade Organization (WTO) on June 10, 2014 and a request for consultations with the Dispute Settlement Body (DSB) of the WTO as a third party. The Government through the Ministry of Trade will be sent a letter of objection to the European Union on the decision. The objection letter will be sent to embassies in Jakarta. Delivery of the letter will be done by the government through the Ministry of TradeKeywords : European Union, Dumping Practices, Economic, Indonesian, Biodiesel,Allegations